2003
DOI: 10.1111/j.1151-2916.2003.tb03301.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Crystallization of Hydroxyapatite Coating Layer Formed by Electron Beam Deposition

Abstract: To improve the biocompatibility of Ti-based metal implants, a hydroxyapatite (HA) coating layer was formed on the surface by electron-beam deposition. The dissolution rate of the coating layer was strongly dependent on the layer's calcium/ phosphorus (Ca/P) ratio. Layers with a Ca/P ratio close to that of crystalline HA (Ca/P ‫؍‬ 1.67) showed good stability in a physiologic saline solution. When the layer was crystallized by heat treatment in air at temperatures between 400°and 500°C, the stability was enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The holes for the implantation were drilled using a low-speed rotary instrument with profuse saline irrigation. The diameter of the drill was successively increased, and the insertion sites were finalized with a 3.75 mm tap without countersinking [19]. After a healing period of 4 weeks, the rabbits were sacrificed and, in each case, the bond strength between the bone and the implant was measured with a torque measurement device (Shinsung Co., Seoul, Korea).…”
Section: Biological Propertiesmentioning
confidence: 99%
“…The holes for the implantation were drilled using a low-speed rotary instrument with profuse saline irrigation. The diameter of the drill was successively increased, and the insertion sites were finalized with a 3.75 mm tap without countersinking [19]. After a healing period of 4 weeks, the rabbits were sacrificed and, in each case, the bond strength between the bone and the implant was measured with a torque measurement device (Shinsung Co., Seoul, Korea).…”
Section: Biological Propertiesmentioning
confidence: 99%
“…et al (2006) electron gun are directed towards the surface of the source material kept in a crucible. The characteristics of the HA coating layer on the Ti surface formed by electron beam deposition have been reported by Kim et al (2003). The Ca/P ratio of the coating layer had a strong infl uence on its dissolution behavior.…”
Section: 5mentioning
confidence: 93%
“…The rapid dissolution results in structural decohesion within the coating, resulting in a very short service life. A semi-crystalline system is more effective in which the amorphous regions undergo rapid dissolution releasing bone-forming ions, while the crystalline phase provides the structural integrity (Kim et al , 2003). Several investigators have studied the changes in plasma spray coated samples immersed in various media like water, SBF, Hanks' balanced salt solution (HBSS), Ringer solution, etc.…”
Section: © Woodhead Publishing Limited 2012mentioning
confidence: 99%
“…New promising techniques and experimental conditions for depositing HAp‐based coatings on metal substrates for biomedical applications have been exploited along the time. By now, a large number of techniques have been employed to obtain HAp coatings on metallic implants, such as electrochemical deposition, sol–gel method, plasma spraying process, electron beam sputtering method, pulsed laser deposition, electrophoretic deposition, ion beam sputtering method, hot isostatic pressing, and biomimetic deposition . However, it has been demonstrated that even though HAp has exceptional biocompatible and bioactive properties, HAp coatings have the ability to facilitate also the proliferation of bacterial cells.…”
Section: Introductionmentioning
confidence: 99%